Neuroimaging, Etiology, Clinical Findings, and Evaluation of Associated Problems in Children with Cerebral Palsy. - BEZGİN, Sabiha; AKBAŞ, Yılmaz; KULE, Gamze (Romanian Journal of Physical Therapy / Revista Romana de Kinetoterapie)
Introduction: Cerebral palsy (CP) is the most common cause of motor impairment in childhood. Its incidence in our country is 4.4/1000 live births. Although motor dysfunction forms the basis of the clinic in cerebral palsy, epilepsy, speech, hearing, vision, nutrition and learning disorders, and many orthopedic problems may accompany this condition. Aim: This study examined CP types, neuroimaging findings, etiologies, clinical findings, and nutritional status of pediatric patients with CP who applied to our hospital. Material and methods: The files of patients aged 1-18 years with CP who applied to Hatay Mustafa Kemal University Medical Faculty Hospital between 01/09/2019-01/09/2020 were retrospectively scanned. The etiology, clinical findings, additional problems accompanying the clinic, and brain magnetic resonance images (MRI) of the patients included in the study were evaluated. Results: Forty eight patients were included in the study. Of the patients with a mean age of 4.9±3.5 years, 33 (68.8%) were male. Spastic CP was present in 93.7% of the patients. Considering the subgroups of patients with spastic type CP, the most common was quadriplegic CP (42.2%). The most common etiological factor was prematurity (56.4%). When we look at the accompanying problems, malnutrition was the most common problem with (72.9%) and epilepsy with a rate of (54.2%). Then came hearing, vision, and speech problems, respectively. When the cranial MRI images of the patients were examined, periventricular leukomalacia (PVL) was the most common MRI finding, with 70.8%. Discussion: We found that prematurity was the most common cause in the patients with cerebral palsy we followed in our region. With the improved newborn conditions, even babies born at short weeks have the opportunity to live. Conclusion: Considering the imaging findings, the first rank of PVL is proportional to prematurity. PVL is a common imaging finding in premature infants.